Leadership Education and Economic Planning: Motivation the Entrepreneurship Learning - Fadhilla Sri Meutia; Fitriyanti Sulaiman; Elihami Elihami; Syarif Syarif (Edumaspul: Jurnal Pendidikan, 2020)
Developing the entrepreneurship training of Islamic studies can be very challenging due to a number of constraints from different aspects, including the formation of regulatory, taxation and economic frameworks that are based on conventional principles of Muhammadiyah University of Enrekang. Much emphasis was given to replication of conventional instruments by restructuring conventional financial products according to the Islamic law of commercial contracts and eliminating prohibitory elements from these products. This paper aims to discuss the role of innovation in structuring contemporary the entrepreneurship training of Islamic studies. A series of library research is conducted by reviewing both classical and contemporary texts in areas relevant to the present study. In addition, we conducted a field study of the practice of innovation made by the stakeholders of the the entrepreneurship training of Islamic studies. It was found that though replication is acceptable, its continuous application may not be suitable. Hence, it is important for leadership management and economic planning and industry experts to think beyond replication. The novelty of this paper lies in the proposed guidelines for innovating Islamic studies